1987
DOI: 10.1159/000288048
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Dreams in Eating Disorders

Abstract: The results of several studies on sleep EEG and dreams in patients with eating disorders are presented and compared with the data obtained in patients with a major depression. The sleep pattern, which is characteristic of depression, could not be found in the eating disorder group. Regarding the cholinergic REM induction test, the depressives displayed a pronounced shortening of REM sleep latency. However, this biological marker, indicating a cholinergic hyperactivity in depression, could not be observed in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
(9 reference statements)
0
13
0
1
Order By: Relevance
“…Among eating disordered patients whose dreams were sampled in a single laboratory night, dreams of food were much more prevalent. One study found them in 58% of patients with bulimia, 26% of patients with anorexia, and 44% of patients with anorexia and bulimia combined (Dippel et al, 1987 ). Similarly, patients with a diagnosis of migraine headache were retrospectively more likely to report taste (31%) and smell (36%) in their dreams than were control subjects (20 and 20%, respectively) (Lovati et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among eating disordered patients whose dreams were sampled in a single laboratory night, dreams of food were much more prevalent. One study found them in 58% of patients with bulimia, 26% of patients with anorexia, and 44% of patients with anorexia and bulimia combined (Dippel et al, 1987 ). Similarly, patients with a diagnosis of migraine headache were retrospectively more likely to report taste (31%) and smell (36%) in their dreams than were control subjects (20 and 20%, respectively) (Lovati et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 24 included studies, 21 could differentiate between melancholic depression, non-melancholic depression, and/or HC. By subgroup, four ( 22 25 ) out of five ( 22 26 ) resting state studies identified one or several EEG parameters that could distinguish groups; among the ERP studies, seven ( 27 33 ) out of nine ( 27 35 ) could separate melancholic depression from the other groups ( 27 33 ), while this was the case in all 10 sleep EEG studies ( 36 45 ).…”
Section: Resultsmentioning
confidence: 94%
“…Regarding the quality of individual studies, 10 studies were classified as of low quality ( 22 , 25 , 28 , 30 , 31 , 34 , 36 38 , 42 ), eight studies as of high quality ( 23 , 24 , 27 , 29 , 32 , 33 , 35 , 40 ), and six studies of moderate quality ( 26 , 39 , 41 , 43 – 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both decreases and increases in REM sleep in anorectics have been reported [40][41][42]. Neil et al [40] demonstrated a longer REM latency, while in the study of Levy et al [21], REM was not affected.…”
Section: Discussionmentioning
confidence: 99%